2019
DOI: 10.1097/prs.0000000000005909
|View full text |Cite|
|
Sign up to set email alerts
|

The Probable Reasons for Dorsal Hump Problems following Let-Down/Push-Down Rhinoplasty and Solution Proposals

Abstract: Background: Nasal hump relapse and its probable reasons or mechanisms have been less discussed after dorsal preservation rhinoplasty. In this article, the authors would like to share their experiences and offer solutions regarding this subject. Methods: Five hundred twenty patients who underwent primary rhinoplasty between the years 2015 and 2017 were included in the study. The push-down method was used for noses with a hump less than 4 mm and the let-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 22 publications
0
53
0
Order By: Relevance
“…Therefore, the LD technique has been advocated for humps >4 mm. 24 In preliminary cadaveric studies at our center, we have found that the PD technique has a narrowing effect on the INV. 25 This is not seen with the LD operation.…”
Section: Management Of the Bony Pyramidmentioning
confidence: 84%
See 4 more Smart Citations
“…Therefore, the LD technique has been advocated for humps >4 mm. 24 In preliminary cadaveric studies at our center, we have found that the PD technique has a narrowing effect on the INV. 25 This is not seen with the LD operation.…”
Section: Management Of the Bony Pyramidmentioning
confidence: 84%
“…Tuncel and Aydogdu reported on 520 patients undergoing successful closed PD or LD surgery with subdorsal cartilage resection. 24 Ishida et al, using a midseptal cartilage strip resection technique without preservation of the dorsal keystone, note satisfactory functional and aesthetic results in a series of 120 patients. 5 No patientreported measures or evaluation of nasal obstruction is discussed in either of these studies.…”
Section: Surgical Outcomes and Challengesmentioning
confidence: 99%
See 3 more Smart Citations